Safety and Security of Passenger Terminal: the Case Study of Riga International Coach Terminal. (2017) - Gromule, Vaira; (Jackiva), Irina Yatskiv; Pēpulis, Juris
Abstract: This paper presents the Riga International Coach Terminal safety and security management system. Authors analyse European documents and tendency to ensure adequate security in the operation of Passenger Terminal and present RICT security risk-based decision-making approach. It is based on the security organization setup, which includes interfaces with internal and external bodies and strategy based on risk management, implemented through a structured security, risk management process. These results and initiatives in Riga International Coach Terminal are important steps to create safeguard of the "sustainability" perspective, which implementation in whole redefine the RICT reliable node of public transport.